Professional services marketing handbook : how to build relationships, grow your firm and become a client champion - Clark, Nigel; Nixon, Charles (2015)
"Marketing in professional services and consulting businesses (law, accounting, property, management consulting, project management, engineering, technical services, etc.) has progressed significantly in recent years. It is now seen as a major contributor to attracting and retaining clients, building a successful brand, and growing revenue and profit.Professional Services Marketing Handbook covers key issues in business development, operations, and delivery and includes case studies, insights, and advice on CRM, digital and social media, thought leadership, branding, and client thoughts to provide the tools to deliver greater business impact"--
"The market for professional services and consulting firms is changing, driven by evolving and more demanding client requirements. Legal, accountancy and other professional services firms are now looking for a new breed of leaders with the insight to help deliver those requirements. Professional Services Marketing Handbook, published in association with the Professional Services Marketing Group, is for marketing and business development professionals, sales specialists, and a firm's technical practitioners who want to play a fuller role in their firm's obsession with client relationship development to increase their impact and influence. Featuring international case studies and best practice from industry leaders and experts such as Allen & Overy, Baker & McKenzie, Jacobs, PwC, Reeves & Co and White & Case, Professional Services Marketing Handbook explains how to become a complete client champion - the voice of the client - to both shape and deliver a firm's client solution and experience. It helps marketers develop a growth strategy for their firm, understand and connect with clients more deeply and develop and manage client relationships to build successful brands"--
Includes bibliographical references (pages 251-252) and index.
Keywords: Consulting firms; Marketing; Professions -- Marketing; BUSINESS & ECONOMICS / Consulting; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Marketing / General; Print books